Innovation-promoting impacts of public procurement - Elvira Uyarra; Oishee Kundu; Raquel Ortega-Argiles; Malcolm Harbour (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2023)
The use of public procurement to advance innovation but also other social, environmental and public service delivery goals has been high in the innovation policy debate in the last two decades. Drawing from the literature on the economics of innovation and innovation policy, this paper provides an overview and critique of the key debates surrounding public procurement of innovation, specifically the rationales, means and challenges associated with its use as an innovation policy tool. We note that despite strong academic interest and policy activity in this area, strategic public procurement to promote innovation is still unevenly adopted. The evidence base is also weak in terms of the methods and data to understand its impact. We argue more research is needed to quantify the outcomes of procurement interventions in different national and sectoral contexts and their integration with other innovation policy instruments.
Keywords: 330; Public procurement; Innovation; Regulation; Public policy; Evaluation